Effect of Injection Botox in Masseter Muscle on Morphometric Measurements of The Mandible in Sprague Dawley Rats - Iram, Maria; Kiani, Muhammad Rizwan Bashir; Qamar, Khadija; Saleem, Saima; Atta, Muhammad Fahad; Zakria, Iram (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the effects of injection botox in masseter muscle on the morphometric measurement of underlying mandible and total body weight change in Sprague Dawley rats.Study Design: Laboratory-based experimental study.Place and Duration of Study: Anatomy Department, Army Medical College, Rawalpindi, with collaboration with Military Hospital, Rawalpindi and National Institute of Health (NIH), Islamabad, from Jun to Aug 2020.Methodology: Female sprague dawley rats, 10 weeks of age, weighing 200-250 gm were selected. They were housed in separate cages in animal house of NIH under standard laboratory conditions and received regular diet and water ad libitum. Animals were divided into three groups. Group-A served as control while group B and C were experimental groups. Group-B was sham injected whilst group-C was injected by injection botox in left masseter muscle. Initial and final weights of the rats were recorded. All the rats were sacrificed after completion of experimental period. Weight of left mandibles was recorded. All the specimens of mandibles were cleaned and the mandibular length, condylar head length and width were measured by Vernier caliper.Result: Total 30 sprague dawley rats were included in the study. Injection botox decreased the morphometric measurements of the mandible in experimental group-C when compared with control group-A and sham group-B with the statistically significant result (p